Patent Trolls as Intruder in Intellectual Property Rights - Kamini Singh; L.S. Gangwar; Vimal Singh (International Journal of Social Sciences Review, 2023)
An inventor who obtains a patent is given the only authority to create, utilize, and market a particular invention for a given period. No one else may utilize the innovation after the right has been granted without a valid license from the patentee. Such inventors are legally protected by this privilege from any harm. Later, it is typically anticipated that the creator will use it by granting licenses to various other producers to introduce it to the consumer market. However, several of these inventors have recently abused the rights that are granted to them. Recently, numerous people have been patenting products in the most ambiguous way that the legal system would permit, with no intention of ever using the patent. They frequently want to make money by suing people or businesses who use products that are even vaguely comparable to their patented product in infringement cases. Patent trolling is the practice in question. Thus, the activity of obtaining and using patents for licensing or legal proceedings rather than for the creation of one's own goods or services can be described as patent trolling; this is because "its real business model is patent trolling." Therefore, we are attempting to describe the aspects, strategies, and methods of patent trolling in this paper and how to cope with them.